Saberes docentes na organização do ensinio-aprendizagem: uma construção reflexiva com professoras do ensino fundamental - Nascimento, Débora Maria do (2011)
The present study has the objective to analyze with teachers from Elementary School the knowledge mobilized in the organization of the teaching-learning process, and its implications in the exploitation of that process. The investigation was developed with two teachers from the first years of the Elementary School, from a public school in Pau dos Ferros-RN. It adopts as basis the notion of knowledge as a set of individual and social relations that the individuals maintain with the world and with themselves, in the teaching and learning relation. (CHARLOT, 2000). It considers yet that the knowledges are immediate processes, reconstructed and mobilized by the practice of reflection, in dialogical and interactional contexts in contact with others. (BAKHTIN, 2002, 2003; VYGOTSKY, 1991, 2004, 2005). The collaborative approach was the theoretical and methodological background that oriented the investigative-educative process. By choosing a collaborative research as basis of the investigative pathway, it starts from the knowledge that the critical and collaborative reflection developed with the teachers from the first years of the Elementary School contribute to explicitate and resignify the meanings assigned to the knowledges that these teachers mobilize in the organization of the teaching-learning and its implications in this process. The results of the reflexive and investigative process developed with the teachers demonstrate that the familiar, scholastic, academic, professional, and the work knowledges lived, constitute the consciousness of being a teacher, and that these knowledges implicate in the dynamics of the process of teaching-learning, but not always the teachers take consciousness about these knowledges. The critical and collaborative reflection, mediated by the actions of describing, announcing, facing and reconstructing allowed to the participants of the research to realize the knowledges of themselves and of the other, the difficulties and possibilities in the organization of the teaching-learning process